Applied solid state science : advances in materials and device research - Wolfe, Raymond (Academic Press, 1972)
Applied Solid State Science: Advances in Materials and Device Research, Volume 3 covers reviews that are directly related to the two devices which are the epitome of applied solid state science - the transistor and the laser. The book discusses the physics of multilayer-gate IGFET memories; the application of the transient charge technique in drift velocity; and trapping in semiconductors and in materials used in xerography, nuclear particle detectors, and space-charge-limited devices; as well as thin film transistors. The text describes the manipulation of laser beams in solids and discusses.